Design, Fabrication, and Application of Stretchable Electronic Conductors - Cheng, Bin; Zhuo, Jingting; Zhou, Yao; Chen, Jiaxiang; Cao, Lingyun; He, Jiangfeng; Chen, Zhihong; Ma, Xiaoxiao; Wang, Juan; Li, Honglong; Yang, Guowei; Yi, Fang (Nano-Micro Letters, 2026)
Stretchable electronics have been recognized as intriguing next-generation electronics that possess huge market value, and stretchable electronic conductors (SECs) are essential for stretchable electronics, which not only can serve as critical functional components but also are the indispensable electronic connections bridging various electronic components within stretchable electronic systems. Herein, we offer a comprehensive review of recent progress in SECs including the material categories, structure designs, fabrication techniques, and applications. The characteristics, performance enhancement strategies, and application requirements are emphasized. Based on the recent advances, the existing challenges and future prospects are outlined and discussed. Highlights: 1 A comprehensive review of recent advances in stretchable electronic conductors including the material categories, structure designs, fabrication techniques, and applications. 2 A novel emphasis on the characteristics, performance enhancement strategies, and application requirements of stretchable electronic conductors. 3 An exhaustive analysis of the existing challenges and future prospects for stretchable electronic conductors.